Universal Grammar as a System for First Language Acquisition and Development: A Critical Review - Husain Abdulhay (Universitas Sebelas Maret, 2026)
Contention of Universal Grammar hypothesis is not a phantom so long as every cut-and-dried assumption and proposition is amenable to sustaining discredit and falsification. Cognitive scholars and linguists mesmerized by the trendy adherence to new presumptions; thanks to typological studies on numerous diverse languages, concur that children recruit different models of thinking which is nowise specific to a sire language. In an attempt to broach the assumption that language is too convoluted and complicated for human to learn, Chomskyan linguists have incubated on the idea of universal grammar for decays, by trying to inculcate their inferences and illations into language studies. To that end, this overview endeavors to zero in on and challenge universal grammar represented as a reproductive mechanism defying any developmental learning. Thus, universal grammar as a springboard for acquisition of language is set out for discussion regarding its lacuna, deficits, and drawbacks apropos of first language acquisition to enable a plausible conception of this premise, as being in vogue for decades. A broader footwork, discussing of suggestions, arguments, and empirical and theoretical evidences, will ensue.